Hyperbaric oxygen therapy is not associated with oxidative stress assessed using plasma F2-isoprostanes and isofurans. (December 2017) - Corcoran, Tomas; Ting, Sonya; Mas, Emilie; Phillips, Michael; O'Loughlin, Edmond; Barden, Anne; Mori, Trevor A.
Abstract: Background and aims: Hyperbaric oxygen (HBO) therapy is increasingly used in medical practice as a means of enhancing the formation of collagen matrix and angiogenesis, thus promoting healing in wounds and necrotic tissue. However, there are concerns that oxygen can also associate with increased production of oxygen free radicals and oxidative stress. F2 -Isoprostanes (F2 -IsoPs) formed by non-enzymatic oxidation of arachidonic acid (AA) are reliable measures for assessing oxidative stress in vivo . In addition, under conditions of high oxygen tension isofurans (IsoFs) are preferentially formed from AA and are considered to better reflect oxidative stress in the setting of high oxygen tension. This study aimed to measure plasma IsoFs and F2 -IsoP in patients receiving HBO therapy to treat osteonecrosis secondary to radiation therapy. Our hypothesis was that IsoFs would continue to rise with increasing oxygen pressures in contrast to F2 -IsoPs whose synthesis would be reduced. Methods: Twelve patients receiving hyperbaric therapy to treat osteonecrosis secondary to radiation therapy were studied during hyperbaric treatment. Blood samples were collected prior to, during and after cessation of HBO therapy that lasted for 119 min. Seven serial blood samples were collected for measurement of plasma F2 -IsoPs and IsoFs, blood gases and haemoglobin. Results: Oxygen saturation and venous oxygen partial pressure (PvO2 ) rose significantly during hyperbaric therapy. However, there were no significant changes in plasma IsoFs or F2 -IsoPs during the hyperbaric therapy session. Conclusion: In this study of patients with osteonecrosis, HBO therapy at a maximum pressure of 2.4 atm with up to 100% oxygen did not worsen oxidative stress assessed using plasma F2 - IsoFs and IsoPs. Highlights: Hyperbaric oxygen (HBO) therapy can potentially cause whole body oxidative stress. Oxidative stress markers were studied in patients undergoing HBO therapy. HBO therapy for 119 mins lead to increased oxygen saturation and PvO2 . HBO therapy did not alter oxidative stress (plasma F2 -isoprostanes or isofurans). HBO therapy is safe and does not adversely affect whole body oxidative stress.